Inhibition of α1‐adrenoceptor reduces TGF‐β1‐induced epithelial‐to‐mesenchymal transition and attenuates UUO‐induced renal fibrosis in mice. Issue 11 (16th September 2020) - Ren, Huiwen; Zuo, Shengkai; Hou, Yayan; Shang, Wenlong; Liu, Na; Yin, Zhuming
Abstract: Renal fibrosis is a common pathological hallmark of chronic kidney disease (CKD). Renal sympathetic nerve activity is elevated in patients and experimental animals with CKD and contributes to renal interstitial fibrosis in obstructive nephropathy. However, the mechanisms underlying sympathetic overactivation in renal fibrosis remain unknown. Norepinephrine (NE), the main sympathetic neurotransmitter, was found to promote TGF‐β1‐induced epithelial‐mesenchymal transition (EMT) and fibrotic gene expression in the human renal proximal epithelial cell line HK‐2. Using both genetic and pharmacological approaches, we identified that NE binds Gαq‐coupled α1‐adrenoceptor (α1‐AR) to enhance EMT of HK‐2 cells by activating p38/Smad3 signaling. Inhibition of p38 diminished the NE‐exaggerated EMT process and increased the fibrotic gene expression in TGF‐β1‐treated HK‐2 cells. Moreover, the pharmacological blockade of α1‐AR reduced the kidney injury and renal fibrosis in a unilateral ureteral obstruction mouse model by suppressing EMT in the kidneys. Thus, sympathetic overactivation facilitates EMT of renal epithelial cells and fibrosis via the α1‐AR/p38/Smad3 signaling pathway, and α1‐AR inhibition may be a promising approach toward treating renal fibrosis.